(untitled) (Texas Journal of Medical Science, 2026)
This study investigates the role of comorbidities in the course of bronchopulmonary diseases among military personnel. Comorbid conditions were identified in 59.3% of patients. The most common were gastrointestinal diseases (37.7%), cardiovascular diseases (10.6%), kidney diseases (7.7%), and diabetes mellitus (3.3%). Cardiovascular diseases (OR=19.6; p